Spot the odd one out: do snake pictures capture macaques’ attention more than other predators? - Zeller, Karl; Ballesta, Sébastien; Meunier, Hélène; Duboscq, Julie; Morino, Luca; Rimele, Adam; Bonnet, Xavier; Maille, Audrey; Dezecache, Guillaume; Garcia, Cécile (Animal cognition, 2023)
Detecting and identifying predators quickly is key to survival. According to the Snake Detection Theory (SDT), snakes have been a substantive threat to primates for millions of years, so that dedicated visual skills were tuned to detect snakes in early primates. Past experiments confronted the SDT by measuring how fast primate subjects detected snake pictures among non-dangerous distractors (e.g., flowers), but did not include pictures of primates’ other predators, such as carnivorans, raptors, and crocodilians. Here, we examined the detection abilities of N = 19 Tonkean macaques ( Macaca tonkeana ) and N = 6 rhesus macaques ( Macaca mulatta ) to spot different predators. By implementing an oddity task protocol, we recorded success rates and reaction times to locate a deviant picture among four pictures over more than 400,000 test trials. Pictures depicted a predator, a non-predator animal, or a simple geometric shape. The first task consisted of detecting a deviant picture among identical distractor pictures (discrimination) and the second task was designed to evaluate detection abilities of a deviant picture among different distractor pictures (categorization). The macaques detected pictures of geometric shapes better and faster than pictures of animals, and were better and faster at discriminating than categorizing. The macaques did not detect snakes better or faster than other animal categories. Overall, these results suggest that pictures of snakes do not capture visual attention more than other predators, questioning previous findings in favor of the SDT.